Effectiveness of the RSQ1 device recuperation protocol in the treatment of sports injuries - Kovacic, I.; Bisic, A.; Nedovic, N. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Injury during sports activities (sports injury) is common in case of insufficient preparation and warm-up before training, due to fatigue and too strenuous training, as well as during uncontrolled exercises on equipment in the gym. RSQ1 device (Physicare International B.V., Zaandam, The Netherlands) is a unique device for neuromuscular stimulation with a high-frequency signal of over 10kHz. Its advantages compared to other devices for electrotherapy: it accelerates circulation almost instantly, creates hypertrophy, increases saturation, engages a large number of motor units as well as a quick analgesic effect. METHODS: Case study: Our subject is 24 years old female professional basketball player, with 14-16 hours spent on the court (including a game as well) per week. During one practice, while sprinting, sharp pain appeared on the lateral side of the quadriceps muscle. After positive (painful) palpation and slight strength testing, a radiologist specialist performed an ultrasound (US) diagnostic. It was confirmed muscle tear (grade II) of m. vastus lateralis and the size of the tear was 1,2 cm wide. Hemorrhage and liquid around the injured tissue were present as well. It was suggested 3 weeks of rest with physical therapy included and US control every 7 days. First time during the rehab of sportsmen with muscle tear the RSQ1 recuperation protocol included 24hrs on the injured muscle. Only during the bathing and physical therapy sessions (cryotherapy, magneto therapy, laser, and interferential current therapy - which lasted one hour), RSQ1 was removed. Immediately after the therapy session, RSQ1 was put back on injured place and a recuperation protocol was set. During the RSQ1 session, electrodes are placed on the injured limb. The injured athlete is trained to use this device at home and keep it working on 24hrs per day. RESULTS: After 3 days of being injured, the athlete felt capable to use muscle more without pain so the isometric exercises for the quadriceps muscle were included together with the RSQ1 device on it. Seven days after the injury, a US diagnostic was done with results of only a visible 0,8 cm muscle tear and almost complete disappearance of hemorrhage and local liquid. Fourteen days after the injury, the US showed that there is not any tear noticeable on the injured area. RSQ1 device is now also included during the process of isometric and concentric exercises for quadriceps muscle. Recuperation protocol was still constantly included. CONCLUSION: Three weeks after the injury, the US showed no signs of injury and the dynamometry testing showed only 15% less strength in the injured leg than before the injury. According to the manufacturer, this protocol results in an increased blood flow and a higher saturation of the blood in the treated area (goes up to 30%), which causes a faster recuperation of the muscle tissue. The athlete was able to return to the court earlier than expected.